Review of Article 34 Paragraph (1) of the 1945 Constitution concerning Handling Abandoned Children (Case Study of the Labuhanbatu Regency Social Service) - Fatwa Sari; Toni Toni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Whereas abandoned children are children whose parents are unable to take responsibility and are unable to meet their basic needs due to economic factors, and the family is not harmonious. This type of research uses Juridical Empirical Research. While empirical juridical is a legal research method that looks at the law directly in looking at direct social facts that distinguish facts from norm values. Research Objects Labuhanbatu Social Service The research results if viewed from the Act Article 34 paragraph (1) that "the poor and neglected children are cared for by the State" in the sense that the Government has responsibility for the development and handling of neglected children. Furthermore, Article 28B Paragraph (2) which states "that the state is obliged to guarantee the right of every child to survival, growth, and develop, as well as the right to protection from violence, exploitation and discrimination. If it is seen from the issue of neglected children in the application of the article, it is still not optimal. Meanwhile, in handling abandoned children, the Labuhanbatu Social Service is still not optimal due to the limited impact of the Covid-19 outbreak for almost three years and the spread has not stopped. The Department of Social Affairs in this case tries to be maximal in handling neglected children with evidence of an emotional approach, in the form of data collection and fostering child survival.